2012
DOI: 10.1186/1477-7517-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Reducing widespread pipe sharing and risky sex among crystal methamphetamine smokers in Toronto: do safer smoking kits have a potential role to play?

Abstract: BackgroundCrystal methamphetamine smoking is associated with many negative health consequences, including the potential for transmission of hepatitis. We examined whether or not a kit for crystal methamphetamine smoking might have some potential to reduce the negative health effects of crystal methamphetamine smoking.MethodsFive focus groups were conducted with crystal methamphetamine smokers recruited by community health agencies and youth shelters in Toronto, Canada. Target groups included homeless/street-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Oceania is the region with the highest prevalence of amphetamine-type substance (ATS) use, with Australia and New Zealand (NZ) having the highest annual estimates of 2.7% and 2.1%, respectively. One major indication of the health risks of ATS is the increased proportion of women requiring comprehensive health and mental health services in both the US and internationally (Jones et al, 2011; Wechsberg et al, 2010; Wright et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Oceania is the region with the highest prevalence of amphetamine-type substance (ATS) use, with Australia and New Zealand (NZ) having the highest annual estimates of 2.7% and 2.1%, respectively. One major indication of the health risks of ATS is the increased proportion of women requiring comprehensive health and mental health services in both the US and internationally (Jones et al, 2011; Wechsberg et al, 2010; Wright et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Additional items packed in these kits may include educational materials, lip balms, disinfectant wipes and condoms . The availability of these kits may potentially increase the engagement with health‐care services (including harm reduction services) and decrease injuries attributable to hot, damaged and/or makeshift pipes among people who smoke methamphetamine . However, qualitative assessments indicate that pipe‐sharing is an integral component of the social experience of methamphetamine smoking .…”
Section: Declarations Of Interestsmentioning
confidence: 99%
“…The availability of these kits may potentially increase the engagement with health‐care services (including harm reduction services) and decrease injuries attributable to hot, damaged and/or makeshift pipes among people who smoke methamphetamine . However, qualitative assessments indicate that pipe‐sharing is an integral component of the social experience of methamphetamine smoking . For a small minority of people who smoke methamphetamine, this risk behavior is a consequence of lack of access to unused pipes due to poverty .…”
Section: Declarations Of Interestsmentioning
confidence: 99%
“…Some studies in Iran have found that active drug use is one of the main factors affecting both positive prevention (9) and access and use of the services among people who live with HIV/AIDS (10). Even among noninjecting methamphetamine users, the risk of pipe sharing is high, leading to an increase in the risk of blood born viruses' transmission, mainly hepatitis C transmission (11).…”
Section: Introductionmentioning
confidence: 99%
“…There are evidences that show methamphetamine harm reduction programs have positive effects on reducing HCV transmission, improving client general health status, and even reducing injection among methamphetamine users (11,12). drugs (PWUD) (13) and its effects on patients who were undergoing opioid substitution therapy (14).…”
Section: Introductionmentioning
confidence: 99%